1911
DOI: 10.1007/bf02149172
|View full text |Cite
|
Sign up to set email alerts
|

Die Konzentrationsarbeit der Niere

Abstract: VIII.Aus der medizinischen Klinik zu GSttingen. Die Konzentrationsarbeit tier Mere. (]Nach gemeinschaftlich mit F. Stromeyer, E. I~Sskuchen und w eiland lt. Miiller ausgefiihrten Untersuchungen.) Von L. Liehtwitz. Die Funktion der Niere, osmotische Arbeit zu leisten, und der Streit der Meinungen, der um die Erkenntnis des Gesehehens bei dieser Verriehtung, um die Giiltigkeit der Auffassung yon C. L u d w i g oder R. Heidenhain gefiibrt wurde, ist in diesem Archly aueh in den letzten Jahren so eingehend eriirte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1923
1923
1945
1945

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In 1 other case the urinary chloride response has not been essentially different from the normal, either on unrestricted or on low salt intake; this was a relatively mild case, an adult with a daily urine output of 4 to 5 liters. Various observers (5,6,7,8,9,10,11,12,13) have reported that chloride elimination may be delayed in diabetes insipidus but in only a few cases has the blood been followed or the urine course of the first few hours observed.…”
Section: Resultsmentioning
confidence: 99%
“…In 1 other case the urinary chloride response has not been essentially different from the normal, either on unrestricted or on low salt intake; this was a relatively mild case, an adult with a daily urine output of 4 to 5 liters. Various observers (5,6,7,8,9,10,11,12,13) have reported that chloride elimination may be delayed in diabetes insipidus but in only a few cases has the blood been followed or the urine course of the first few hours observed.…”
Section: Resultsmentioning
confidence: 99%